THE ANALYSIS OF EDUCATIONAL MARKETING MIX MODEL AND THE INFLUENCE ON STUDENT'S CHOICE TO STUDY IN SMA BPK PENABUR TASIKMALAYA - Heryanto (2013)
Recent time, schools must be competitive to get students who like to enter. SMA BPK PENABUR Tasikmalaya as a private school has to compete with other state schools which are good for students. The problem from SMA BPK PENABUR Tasikmalaya is many graduated junior high schools entered the state schools. Marketing mix model is used to influence student's choice to enter the school. Here,educational marketing mix model consists of product, place, price, promotion, people, process and psychical evidence analyzed. The objectives from this research is to analyze the influence of product, product, place, price, promotion, people, process and psychical evidence on the student's decision to enter SMA BPK PENABUR Tasikmalaya. Based on Jobber's theory (2011),by analyzing this marketing mix model, it is hoped to know the influence of them on student's choice. By then, the object here is students of SMA BPK PENABUR in current three years. In which, 100 students are used as sample by using Slovin'sformula Research method of this study is descriptive in which questionnaire used. Then the data got was analyzed by using multiple linear regression. The current study took nearly seven months to be completed, January 2013 to July 2013, held in SMA BPK PENABUR Tasikmalaya. And the result show that product, price, promotion and people influence the student's choice to enter SMA BPK PENABUR Tasikmalaya. Then, the rest ones, place, process and psychical evidence don't influence on student's choice. Key Words: markting mix, product, place, price, promotion, people, process, psychical evidence